Effect of thickness on defects of air forced dried oil palm lumber (OPL) - Chang, Ying Ying (2018)
Air forced drying is a method to dry oil palm lumber (OPL) by forcing the air circulation towards the OPL by setting a range for air velocity. This method takes shorter time compared to the conventional air drying method. OPL has high initial moisture content and is prone to drying defects like warping, checks and collapse. Conventional air drying method for OPL results in high number of defects. In this study, air forced drying method is used to determine the effect of thickness of OPL on the drying defects. The two thicknesses of OPL in this study are 3cm and 5cm. The samples were cut according to their size and stacked properly to undergo air forced drying. After the duration of one month, the defects found on the samples were evaluated based on 3 categories of defects and percentage of defects in each thickness group was calculated. The rate of drying of the samples were determined by measuring the weight of samples each day and calculated with formula. From the data, the thickness of OPL has significant effect on the level of defects. The 3cm thick OPL is more prone to drying defects than the 5cm thick OPL by air forced drying method.